Dissimilar linear friction welding of selective laser melted Inconel 718 to forged Ni-based superalloy AD730™: Evolution of strengthening phases. (10th January 2022) - Tabaie, Seyedmohammad; Rézaï-Aria, Farhad; Flipo, Bertrand C.D.; Jahazi, Mohammad
Abstract: The continuous growth in the manufacture of aerospace components such as blisks has led to an increase in the application of different hybrid materials fabricating methods, and thus the requirements for joining and strengthening of dissimilar welds. According to this goal, selective laser melted (SLM) Inconel 718 was joined with forged AD730™ Nickel-based superalloy through linear friction welding (LFW) in this study. Microstructure variation, specifically with respect to secondary phases precipitation was investigated. The microhardness and strengthening mechanisms of the weldment were also studied. The precipitation (volume fraction and size of particles) at different regions of both sides of the weld line was characterized. Close to the weld line, the dissolution of γ'/γ" and Laves phases and grain refinement occurred which reveals the effects of both compression strain and high temperature on recrystallization and high degree of elemental diffusion in the weld zone (WZ). It is shown that the size, volume fraction, and shape of secondary phases increased and changed (from spherical to long-striped for Laves particles) as we went from the WZ toward the base metal. However, the measured microhardness indicated that the strength of AD730™ alloy depends significantly on the grain size, while strength in SLM Inconel 718 was dominated by shape (or size) and the presence of secondary phases (γ'/γ" and Laves). Graphical abstract: Image, graphical abstract